Preparation and structure optimization of 2D MXene nanocomposites for microwave absorbing application - Yang, Ping-an; Deng, Wenjiao; Luo, Jiufei; Li, Rui; Li, Penghua; Yin, Yichen; Huang, Xin; Zhang, Yuxin (Materials today physics, 2024)
With the increasing application of electromagnetic waves (EMWs), issues related to electromagnetic (EM) radiation and interference have become more prominent, rendering research on EMW absorbers a highly topical subject. 2D MXenes have emerged as up-and-coming EM-absorbing materials due to their inherent characteristics. These include high electrical conductivity-induced strong dielectric loss, abundant surface functional groups enhancing dipole polarization and facilitating processing, and a large specific surface area providing an effective contact area with more active sites. However, achieving excellent EMW absorption performance across a wide bandwidth is challenging for MXenes due to their high conductivity, defects, and surface functional groups, resulting in the high dielectric constant, as well as their single loss and lack of magnetic loss. To tackle these issues, researchers primarily adjust the layer spacing, surface functional groups, and defects of pure MXenes to achieve superior attenuation capabilities by optimizing the preparation methods. Additionally, researchers optimized the composition and structure of the MXenes-based absorber to create a diverse combination of heterogeneous interfaces, magnetodielectric synergies, and conduction networks, promoting a balance between impedance matching and attenuation capabilities. Herein, based on recent research findings, this work presents the preparation and properties of MXenes and elucidates their correlation with absorption properties. The summary and discussion of absorption characteristics adjustment and attenuation mechanisms optimization of MXene-based absorbers resulting from microstructure design strategies and component optimization strategies are presented. Finally, recent advancements and challenges of MXene-based absorbers are analyzed, particularly emphasizing the microstructure design concept based on microwave absorption mechanisms.